How Does Prior Knowledge Influence Learning Engagement? The Mediating Roles of Cognitive Load and Help-Seeking - Dong, Anmei; Jong, Morris Siu-Yung; King, Ronnel B. (Frontiers in Psychology, 2020)
The aim of this research was to examine how prior knowledge influences learning engagement. A sample of 356 students from two middle schools in the north of China participated in the study. Analyses using structural equation modeling revealed that prior knowledge was positively associated with learning engagement, and that this relationship was singly mediated by cognitive load and jointly mediated by cognitive load and instrumental help-seeking. Cognitive load also mediated the impact of prior knowledge on instrumental help-seeking, executive help-seeking and avoidance of help-seeking. The study shows that students with more prior knowledge and lower cognitive load are able to exercise higher level self-regulated learning strategies, leading to good quality learning engagement. On the other hand, students with less prior knowledge and higher cognitive load are less able to exercise the corresponding strategies, leading to less desirable learning engagement. Based on the research findings, recommendations for how teachers can improve learning engagement through decreasing cognitive load are discussed.